Global Consulting Inc. a study on the collection management practice of an electronic library - Letargo, Ma. Katrina Joy R. (2003)
This study was conducted to determine the effectiveness of the existing content management practice of the Government Consulting Inc. (GCI) Library. The library is a storage of key government information relevant to the GCI organization. To measure this effectiveness, the different components of an effective Collection Management (CM) Program were analyzed. The descriptive method of inquiry was carried out for this study.